Fractional Flow Reserve and Instantaneous Wave‐Free Ratio Predict Pathological Wall Shear Stress in Coronary Arteries: Implications for Understanding the Pathophysiological Impact of Functionally Significant Coronary Stenoses - Christopher C. Y. Wong; Ashkan Javadzadegan; Cuneyt Ada; Jerrett K. Lau; Ravinay Bhindi; William F. Fearon; Leonard Kritharides; Martin K. C. Ng; Andy S. C. Yong (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2022)
Background The pathophysiological mechanism behind adverse outcomes associated with ischemia‐inducing epicardial coronary stenoses and microcirculatory dysfunction remains unclear. Wall shear stress (WSS) plays an important role in atherosclerotic plaque progression and vulnerability. We aimed to evaluate the relationship between WSS, functionally significant epicardial coronary stenoses, and microcirculatory dysfunction. Methods and Results Patients undergoing invasive coronary physiology testing were included. Fractional flow reserve, instantaneous wave‐free ratio, and the index of microcirculatory resistance were measured. Quantitative coronary angiography was used to obtain the lesion percentage diameter stenosis. Computational fluid dynamics analysis was performed to calculate WSS parameters. Multiple regression analysis was performed to calculate the standardized regression coefficient (β) for the coronary physiology indices. A total of 107 vessels from 88 patients were included. Fractional flow reserve independently predicted the total area of low WSS (β=−0.44; 95% CI, −0.62 to −0.25; P<0.001) and maximum lesion WSS (β=−0.53; 95% CI, −0.70 to −0.36; P<0.001) after adjusting for percentage diameter stenosis and index of microcirculatory resistance. Similarly, instantaneous wave‐free ratio also independently predicted the total area of low WSS (β=−0.45; 95% CI, −0.62 to −0.28; P<0.001) and maximum lesion WSS (β=−0.58; 95% CI, −0.73 to −0.43; P<0.001). The index of microcirculatory resistance did not predict either low or high WSS. Conclusions Fractional flow reserve and instantaneous wave‐free ratio independently predicted the total burden of low WSS and maximum lesion WSS in coronary arteries. No relationship was found between microcirculatory dysfunction and WSS.